2017
DOI: 10.1038/cddis.2017.68
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-linked dimerization of BST-2 confers anoikis resistance to breast cancer cells by negating proapoptotic activities to promote tumor cell survival and growth

Abstract: Almost all breast tumors express the antiviral protein BST-2 with 67%, 25% and 8.2% containing high, medium or low levels of BST-2, respectively. Breast tumor cells and tissues that contain elevated levels of BST-2 are highly aggressive. Suppression of BST-2 expression reprograms tumorigenic properties of cancer cells and diminishes cancer cell aggressiveness. Using structure/function studies, we report that dimerization of BST-2 through cysteine residues located in the BST-2 extracellular domain (ECD), leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 38 publications
3
52
0
Order By: Relevance
“…In addition, it has been suggested that increased immune cell adhesion and resistance of cancer cells to tamoxifen-induced apoptosis is linked to BST-2 expression [27,28,30]. We have also shown that the silencing of BST-2 in murine and human breast cancer cell lines results in a shift from a highly aggressive to a non-aggressive phenotype, including loss of cell to cell and cell to ECM adhesion [24,29], decrease in anchorage-independent growth/survival, formation of invadopodia for ECM remodeling, migration, and invasion [31]. Together, these findings suggest a potential for BST-2 as a valuable therapeutic target.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…In addition, it has been suggested that increased immune cell adhesion and resistance of cancer cells to tamoxifen-induced apoptosis is linked to BST-2 expression [27,28,30]. We have also shown that the silencing of BST-2 in murine and human breast cancer cell lines results in a shift from a highly aggressive to a non-aggressive phenotype, including loss of cell to cell and cell to ECM adhesion [24,29], decrease in anchorage-independent growth/survival, formation of invadopodia for ECM remodeling, migration, and invasion [31]. Together, these findings suggest a potential for BST-2 as a valuable therapeutic target.…”
Section: Introductionmentioning
confidence: 68%
“…It has been previously shown that B49 and B49Mod1 possess anti-adhesion activity [32]. Since B49Mod1 contains cysteine residues that mediate BST-2 dimerization [12][13][14] and the adhesion-promoting function of BST-2 [29], we examined the role of cysteine-linked disulfide (S-S) bonds in the anti-adhesion function of B49Mod1. 2 mol equivalents of 1,4-Dithiothreitol (DTT), a reducing agent that reversibly breaks down protein S-S was added to B49Mod1 without quenching the oxidative process followed by incubation at 56 • C for 30 minutes.…”
Section: Cysteine-linked Disulfide Bond Is Important For Anti-adhesiomentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a tumorigenic role of BST2 has been suggested although the mechanism has not been completely clarified. In breast cancer cells, BST-2 mediates cancer cell adhesion and anchorage-independent growth thereby promoting tumor cell survival through inhibition of anoikis [53]. In vascular endothelial cells, IFNγ-induced up-regulation of BST2 mediates adhesion to monocytes [54].…”
Section: Discussionmentioning
confidence: 99%